Pelaksanaan Pembelajaran Menulis Teks Deskripsi Menggunakan Media Canva Siswa Kelas XI-6 SMA N 7 Kota Bengkulu - Miratun Niska; Rio Kurniawan; Didi Yulistio (UNIB Press, 2026)
The purpose of this study was to describe the implementation of learning the introduction, core, and closing activities of writing description text using canva media in class XI-6 SMA N 7 Bengkulu City. This research uses qualitative approach and descriptive method. . The data collection technique in this research is observation technique. Data analysis techniques used in this research are observing, recording, classifying, repeating observing, analyzing, interpreting, and drawing conclusions. According to the study's findings, students in class XI-6 SMA N 7 Bengkulu City are learning how to create descriptions utilizing Canva medium has been carried out in accordance with the 2013 curriculum which includes actions that are introductory, central, and concluding. During the introductory exercises, the instructor welcomed the pupils, students and teachers prayed before learning activities, and students responded actively to the subject information that would be taught, the teacher did not explain the learning objectives. During the core activities, the teacher uses Canva to teach students about the description material, students use Canva to study the description material that has been taught by the teacher, students record important information about the simulated material, the teacher makes a question session about the description material, students return the questions they have, and the teacher gives an example text about the description material. While students and teachers participated in the learning activities, teachers supported the learning activities by guiding students and did not do reflection.